Personal Branding Strategy For Celebrity Doula On Social Media: Case Study on Instagram @jamilatus.sadiyah - Verenia Verenia; Silvanus Silvanus (Communication, 2022)
Celebrities or politicians usually do personal branding, but now many people need personal branding, especially to stand out in a competitive job market. One profession needing personal branding is a doula, which is still unpopular in Indonesia. A doula service became a trend among Indonesian celebrities. Jamilatus Sa’diyah, or Mila, is a doula specializing in birth companions that successfully builds her branding on Instagram. Despite her young age and not having a doula certification, she could build trust from her clients, and many celebrities used her service as a birth companion. People need to do persuasive communication when building their branding. This research uses a concept of eight dimensions of personal branding concept by Montoya to get depth understanding of Mila’s branding. This qualitative-descriptive study uses the post-positivism paradigm with the study case method. The data is gathered through in-depth interviews, online observation, and document studies. Data triangulation will be used, and the data will be analyzed through pattern making and explanation building. Among the eight dimensions, Mila leans towards two dimensions: specialization and personality.